2016
DOI: 10.1016/j.neurobiolaging.2015.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an FTLD-PDB family with the coexistence of SQSTM1 mutation and hexanucleotide (G 4 C 2 ) repeat expansion in  C9orf72 gene

Abstract: The C9orf72 expansion is considered a major genetic cause of familial frontotemporal dementia (FTD) in several patients' cohorts. Interestingly, C9orf72 expansion carriers, present also abundant neuronal p62-positive inclusions. Although p62/SQSTM1 mutations were initially associated with Paget disease of bone (PDB), they have been also identified in FTD. We describe an FTD-PDB family in which the proband presented with behavioral FTD phenotype and concomitant Paget disease. The molecular genetic analysis reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…In this study, we confirmed that mutations in SQSTM1 gene and C9ORF72 expansions may co-occur in patients with PDB, as previously described (Almeida et al, 2016). Therefore, it is possible that both genes may converge into a common pathogenetic mechanism.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, we confirmed that mutations in SQSTM1 gene and C9ORF72 expansions may co-occur in patients with PDB, as previously described (Almeida et al, 2016). Therefore, it is possible that both genes may converge into a common pathogenetic mechanism.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, in a family with FTD and concomitant PDB, the co-occurrence of the P392L mutation in SQSTM1 and the C9ORF72 pathological expansions was recently reported (Almeida et al, 2016).…”
Section: Introductionmentioning
confidence: 97%
“…Whether SQSTM1 mutations in isolation are pathogenic, or whether the altered Keap1-Nrf2 signalling reported here exposes a cellular vulnerability that additional genetic and/or environmental factors combine with to promote neurodegeneration remains unclear. However, it is notable that the G351A mutation of SQSTM1 was identified in a FTLD patient who also had a repeat expansion in C9orf72 ( Miller et al, 2015 ), and similarly in an FTLD-PDB family with SQSTM1 mutation (P392L, within the UBA domain) a C9orf72 expansion segregated with frontal cognitive impairment or dementia (but not PDB) in all but one carrier ( Almeida et al, 2015 ). Molecular evaluation of multiple genes in ALS-FTLD cohorts, as advocated by Almeida and co-workers, is likely to be very informative in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…Variants in numerous genes are associated with susceptibility to ALS-FTLD including SQSTM1 ( Rubino et al, 2012 ), which was previously found to carry muta`tions in patients with the skeletal disorder Paget's disease of bone (PDB) ( Rea et al, 2014 ). Coexistence of PDB and ALS-FTLD is apparently rare and precisely how different SQSTM1 mutations (some of which are common to both disorders) can lead to either neurodegeneration or PDB is currently unknown, although in some cases co-occurrence of an additional mutation such as a pathogenic C9orf72 expansion may account for the neurodegenerative phenotype ( Almeida et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…This complication stems from the rare discovery that mutations in 2 different genes can co-exist in the same individual. Examples of this include, C9orf72/GRN , C9orf72/MAPT, C9orf72/SQST1, C9orf72/TARDP [56, 68, 69]. …”
Section: Clinical Genetic Counseling and Testing Issues For Ad And Ftmentioning
confidence: 99%